2012
DOI: 10.1063/1.4711209
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile floating gate organic memory device based on pentacene/CdSe quantum dot heterojuction

Abstract: An organic floating-gate memory device using CdSe quantum dots (QDs) as a charge-trapping element was fabricated. CdSe QDs were localized beneath a pentacene without any tunneling insulator, and the QD layer played a role as hole-trapping sites. The band bending formed at the junction between pentacene and QD layers inhibited back-injection of holes trapped in CdSe into pentacene, which appeared as a hysteretic capacitance-voltage response during the operation of the device. Nearly, 60% of trapped charge was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 15 publications
(14 reference statements)
0
6
1
Order By: Relevance
“…4, the I ON and I OFF current states are stable up to 1 © 10 4 s with little deterioration at about 4.8 © 10 3 s, because majority of the trapped charges are sustained up to 1 © 10 4 s and have a distinct ON/OFF ratio of 10 4 , which indicates the good data retention stability of the device, as reported elsewhere. [43][44][45] Again, note that the obtained ON/OFF ratio of 10 4 is relatively higher than that obtained in our previous work. 32,33) This long retention time might be attributed to the existence of an extra energy barrier near the heterojunction of PMSSQ2 and CdSe QD nanoparticles.…”
Section: Resultscontrasting
confidence: 66%
“…4, the I ON and I OFF current states are stable up to 1 © 10 4 s with little deterioration at about 4.8 © 10 3 s, because majority of the trapped charges are sustained up to 1 © 10 4 s and have a distinct ON/OFF ratio of 10 4 , which indicates the good data retention stability of the device, as reported elsewhere. [43][44][45] Again, note that the obtained ON/OFF ratio of 10 4 is relatively higher than that obtained in our previous work. 32,33) This long retention time might be attributed to the existence of an extra energy barrier near the heterojunction of PMSSQ2 and CdSe QD nanoparticles.…”
Section: Resultscontrasting
confidence: 66%
“…4,5 The conventional OFET memory devices usually showed unipolar memory properties, meaning that only holes or electrons can be captured as storage charges. 6,7 In this case, the memory window of the OFET memory devices was usually not enough to achieve the distinguishable data storage level, which may affect the accuracy of the readout of the data. Compared to the OFET unipolar memory devices, the OFET memory devices with ambipolar memory properties have a larger memory window because both holes and electrons can work together as storage charges.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular charge storage elements (MCSEs) have great superiority in charge density over the well-investigated nanofloating gate with a designable molecular structure, flexible synthesis, and tunable bandgap. , However, the memory performance is dominated not only by the F–N (Fowler–Nordheim) tunneling barrier between the transport layer and MCSEs but also by several other factors. Because of the polymorphic behavior in the condensed state, the polymer-based MCSEs are ambiguous in charge trapping mechanism; meanwhile, they have several drawbacks such as multistep synthesis and uncontrollable molecular weight. Therefore, using small-molecule compounds as MCSEs is a promising way to realize the high-density information storage with reliable charge maintenance in transistor memory and further clarify the charge trapping mechanism. , Although the investigation in the correlation between charge storage behavior and small molecular MCSEs is limited, there are still some useful results that enlighten us with the design of MCSEs materials, especially from the polymer dielectrics. Kim’s group concluded that the hydrophobic and nonpolar polymers displayed a larger amount of charge storage than that of hydrophilic and polar polymers owing to the rapid dissipation of transferred charges leading to a smaller polarity .…”
Section: Introductionmentioning
confidence: 99%